Reflections on School Science - Mukherjee, Amitabh (Voices of Teachers and Teacher Educators, 2017)
Science, once regarded as challenging, is now considered boring by school students. It is argued that this is because of the way science is taught in schools. Over the last three decades, there has been a trend of including more and more content in syllabi and textbooks, while laboratories have declined. School Science has thus become a collection of facts to be memorised. The Hoshangabad Science Teaching Programme showed that it was possible to create a school science curriculum in which the processes of science received due importance. This was recognised in the NCF 2005 documents. However, much remains to be done, and the community of teachers and teacher educators has to make efforts at various levels to rescue school science from its ‘boring’ tag.